An analysis of the role of young women in peace building in Zimbabwe: the case of ZYWNP in Mutoko 2008-2013. - Thauzeni, Patience (Midlands State University, 2014)
Young women constitute part of the Zimbabwean youth population and have a significant role to play in peacebuilding in Zimbabwe. According to Piazza (2012) youth present the biggest threat to peace consolidation, but also a major opportunity with their energy, innovative mind set and natural optimism. Young women are among the most vulnerable groups during conflict; as a result of this young women have been regarded mostly as victims of war and violence; undermining and ignoring their role in rebuilding communities, building peace and overcoming trauma. Young women are generally categorized under the broad term women thus restricting and undermining their contributions towards peacebuilding. Young women especially in Zimbabwe less privileged societies like Mutoko, Musanhi village have been the link to their community’s development through their membership in varying non-governmental organizations either focusing on human rights, peacebuilding or entrepreneurship. This has helped strengthen family and society structures through implementation of community development projects, and access to information social, political or economic hence creating peaceful coexistence among societies once fragmented by conflict and violence. However these roles and many others by young women remain undermined and sometimes ignored.